Development of Hybrid English Learning Materials Integrated with the Values of Religious Moderation - Septi Anggaira, Aria; Madkur, Ahmad; Setiyana, Leny; Agustina Sari, Yeasy; Aryanti, Nurul (Forum for Linguistic Studies, 2025)
This study sought to design hybrid English learning materials that integrate religious moderation values. It used a research and development design (RnD) consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data were collected both quantitatively via pre-and post-test and qualitatively via students and lecturers’ open-ended feedback and validators’ comments. The setting of the research was an Islamic state university in Lampung, Indonesia where 89 third-semester English Education students and two lecturers were involved. The needs analysis showed that the materials met 83.3% of the lecturers’ expectations and 80% of the students’ needs. The feasibility test results were obtained through a limited user trial of the product via a questionnaire, yielding an average value of 4.3. Validation results demonstrated high effectiveness, with the t-test revealing a significant difference between students’ pre-test and post-test scores (t = 19.137, p = 0.000). The test revealed that Ho is accepted because the value of sig2 tailed = 0.000 > a = 0.005. These findings indicate that the hybrid learning materials integrated with religious moderation values effectively support students’ English language learning and align with both pedagogical goals and cultural-religious contexts in religiously affiliated higher education. This study contributes to broader English language teaching practices by promoting inclusive and culturally responsive pedagogy in both local and global multicultural contexts.